Pengaruh Komitmen Organisasi dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan PT Adis Dimension Footwear - Ferdiyanto , Agung; Rastryana, Ulta (CV Warnak Johanna Nusantara, 2025)
PT Adis Dimension Footwear is a labor-intensive company engaged in the field of sports shoes, where the products produced are exported abroad. The problem that occurs is a decrease in employee performance caused by the variables of organizational commitment and organizational citizenship behavior (OCB). The purpose of this study was to determine how much influence organizational commitment and organizational citizenship behavior (OCB) have on employee performance at PT Adis Dimension Footwear. The method in this study uses the causal associative method. For data collection, researchers used questionnaires to 100 respondents. Based on partial research, it shows that the variables of organizational commitment and organizational citizenship behavior (OCB) have a positive and significant effect on employee performance at PT Adis Dimension Footwear. While simultaneously also shows that there is a significant influence of organizational commitment variables and organizational citizenship behavior (OCB) on employee performance at PT Adis Dimension Footwear which is indicated by the sig value where the resulting sig value is 0.000 <0.05 and the F-count value is 185.348> F-table 3.09. And the coefficient of determination value shows that the organizational commitment and organizational citizenship behavior variables are able to explain employee performance variables by 78.8%, while the remaining 21.2% is explained by other variables outside the variables used in this study.